Clustering based Dynamic Routing Algorithm for Efficient Energy Utilization in Wireless Sensor Networks (WSNs) - Geeta; Bhavikatti, Arvind Mallikarjun (International journal of advanced networking and applications, 2023)
The significance of proper and efficient energy utilization is quite high in Wireless Sensor Networks (WSNs). As a result, network lifetime can be massively enhanced. Therefore, Graph enabled Energy Optimized Routing (GEOR) algorithm is adopted to extend the lifetime of the sensor network and minimize energy consumption in WSNs. An efficient solution for lifetime enhancement of sensor network and energy minimization are key objectives of the proposed GEOR algorithm. The proposed GEOR algorithm provides improved performance than the traditional Low Energy Adaptive Clustering Hierarchy (LEACH) approach. Here, the proposed GEOR algorithm enhances cluster size and the CH selection process is performed to elect CHs for multiple clusters present in the sensor network. A detailed solution for the optimization problem in WSNs is also presented. The mobility aspect of the sink node has a massive impact on energy consumption in WSNs. Experimental results are evaluated in terms of sensor network lifetime enhancement (number of alive nodes and number of dead nodes). Cluster formation and CH selection are performed based on the mobility cost function. Throughput and network lifetime results are obtained in terms of residual energy using the proposed GEOR algorithm. The result is compared against the traditional LEACH approach and the proposed GEOR algorithm shows superior performance.